Pengaruh Media dan Umur Biakan Jamur Metarhizium anisopliae M. terhadap Tingkat Kematian Larva Oryctes rhinoceros L. (Scarabaeidae ; Coleoptera) - NI MADE WINDA UTARI; PUTU SUDIARTA; I GUSTI NGURAH BAGUS (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2015)
ABSTRAK Influence of Media and Fungus Metarhizium anisopliae M. Age culture to Larvae Mortality of Oryctes rhinoceros L. (Scarabaeidae; Coleoptera) Oryctes rhinoceros L. is importance pest that can be serious problem to coconut plantations. The utilization of fungus Metarhizium anisopliae M. as biological agents has became a recommended alternative choice considering its selective and safe infect to ecosystem. The purposes of this study in order to find out the effectiveness rates of media and culture age of fungus M. anisopliae on   O. rhinoceros larvae mortality and to find out the culture age of M. anisopliae in corn and rice media that cause O. rhinoceros larvae mortality. This study used in vitro and direct trial method. The result showing that fungus Metarhizium anisopliae in culture age of 4 weeks have ability to infect the larvae since 6th and on  14th days after application the all of  larvae was infected. On the other hand the fungus in culture age of 3 weeks the  larvae was infected since 7th day after application and on 21st days after application the all larvae was infected. Keywords:, Oryctes rhinoceros L. Metarhizium anisopliae M.